KEPATUHAN PENGGUNAAN 3 KOMBINASI OBAT (TENOFOVIR, LAMIVUDIN, DAN DOLUTERGRAVIR) PADA PASIEN HIV DI POLI RAWAT JALAN RUMAH SAKIT Dr .HAFIZ CIANJUR PERIODE JANUARI 2023 SAMPAI MARET 2023 - Safitri, Bunga; Agustari , Fifi (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Since the use of antiretroviral therapy, the life expectancy of HIV patients has continued to increase. However, prolonged use of drugs results in chronic immune activation so that this group is vulnerable to drug side effects and other complications. The ability of the HIV virus to mutate and reproduce itself when exposed to antiretroviral drugs or known as HIV Drug Resistance (HIVDR) is also a problem of global concern because it can cause treatment failure and further spread of drug-resistant HIV (Anggriani et al., 2019). To determine the relationship between level of knowledge and risk behavior for HIV/AIDS in outpatient clinics at Dr. Hafiz Hospital Outpatient Clinic, quantitative descriptive research with non- parametric statistics, namely bivariate analysis using the chi square test. Quantitatively taken from questionnaire distribution data from this study, the number of patients who had high compliance scores was due to the patient's own intention to undergo treatment so that the virus in his body did not develop. Apart from that, there is high compliance with taking medication because patients really comply with the advice given by doctors and health workers to take medication regularly and according to the provisions given (Srikartika et al., 2019). If we look at employment, the majority of respondents work as 8 employees are HIV patients (40%). If we look at gender, the majority of respondents were male, 13 HIV patients (65%). If we look at compliance, the majority of respondents declared high compliance, namely 11 HIV patients (50%). the results of data analysis using the chi - square test with statistical calculations a = 0.05, obtained a Sig value. (p-value) is 0.101 (>0.05), so it can be concluded that Ho is accepted and Ha is rejected, meaning that there is no significant relationship between the gender variable and Compliance with the Use of 3 Drug Combination for HIV Patients data analysis using the chi - square test with statistical calculations a = 0.05, obtained a Sig value. (p-value) is 0.573 (>0.05), so it can be concluded that Ho is accepted and Ha is rejected, meaning that there is no significant relationship between the work variable and Compliance with the Use of 3 Drug Combinations for HIV Patients